The Bidecadel climate cycle : Alive and well - Malherbe, Johan; Smit, I (2018)
Paper presented at the 34th Annual Conference of South African Society for Atmospheric Science (SASAS 2018), 20-21 September 2018, Ballito, South Africa We consider rainfall variability over the Lowveld in northeastern South Africa during the last 8 decades and demonstrate the persistence of a bi-decadal rainfall cycle in the region. We also note associations with the Southern Annular Mode and with the Southern Oscillation Index together with temporal changes in the association between these two indices, related to the global patterns associated with cycle.